Non-Pharmacological Interventions for Reducing Fear of Childbirth - Gültepe, Remziye (Scripta Medica, 2025)
Fear of childbirth (FOC) is a common psychological condition during pregnancy and can negatively impact maternal and foetal health. Non-pharmacological interventions stand out in the literature as safe and effective strategies for reducing FOC. This review comprehensively examines the effects of methods such as antenatal education programs, cognitive-behavioural therapy, mindfulness-based approaches, yoga and breathing techniques, hypnobirthing and midwife-led continuity models on FOC. The literature search was conducted using studies published in English between 2000 and 2025 in PubMed, Scopus and Web of Science databases. Findings indicate that these non-pharmacological approaches increase pregnant women’s knowledge of the birth process, reduce anxiety and fear and strengthen perceived control during labour. Social support elements such as midwife-led continuity models and partner participation stand out as important factors that increase the effectiveness of interventions. Heterogeneity in the literature regarding the duration, frequency and delivery methods of interventions limits the generalisability of the results. In conclusion, nonpharmacological interventions are effective and feasible methods for the management of FOC; their integration into routine pregnancy care will improve women’s birth experiences and support maternal and child health.